Technical skills competency level among students at vocational colleges in Malaysia - Kamin, Y. B. (American Scientific Publishers, 2017)
Competency is the ability to perform a task which covers aspects of knowledge, skills and attitude which can be derived from experiences and process of learning. This study aimed to identify the technical skills competency level of students. This quantitative research using questionnaires and survey was conducted among mechanical program students at Vocational Colleges in three states. Data were analyzed descriptively in the form of frequency, percentage, mean and standard deviation using Statistical Package for Social Sciences (SPSS) version 22.0. The findings of the study show that the technical skills level of competency for students in Mechanical Program from three courses namely, Automotive Technology, Welding Technology, Air Conditioning And Refrigeration Technology” is at a high level. However, Industrial Machining Technology” students are at a moderate level. Therefore, improvements for each program need to be addressed to ensure that students possess the technical skills competency which are significant for their future undertakings.